Au-decorated Co3O4 nanostructures for plasmonic enhanced PEC sensing of cancer biomarkers - Naz, Gul; Imad, Rehan; Soomro, Razium A.; Alomar, Taghrid S.; AlMasoud, Najla; Karakuş, Selcan; El-Bahy, Zeinhom M. (Applied physics. A, Materials science & processing, 2023)
Low conductivity and rapid charge-carrier recombination are the bottleneck issues for semiconductor-based photoelectrochemical sensors. Herein, we report the development of an efficient photoanode consisting of in-situ grown Co 3 O 4 nanostructures decorated with plasmonic gold (Au) nanoparticles (Au@Co 3 O 4 ). The in-situ growth of Co 3 O 4 on ITO electrodes was achieved through a hydrothermal reaction, followed by the deposition of Au nanoparticles (NPs) via wet-chemical precipitation. The strategy enabled direct contact between Co 3 O 4 and ITO, minimizing charge-carrier leakage, while the Au NPs decoration improved photocurrent responsiveness and reduced charge-carrier recombination through the plasmonic effect and Schottky junction formation. The Au-decorated Co 3 O 4 photoanode (Au@Co 3 O 4 ) was configured for PEC sensing of folate binding proteins (FBP), using folic acid (FA) as a natural FBP receptor. The sensing interface was created by immobilizing FA receptors onto photoelectrodes functionalized with chitosan (Chi). The PEC biosensing was achieved based on protein–ligand interaction, where the decline in the photocurrent response of the mediator molecule, i.e., ascorbic acid, was directly proportional to the concentration of FBP. The constructed biosensor could detect FBP in a low concentration range of 1 × 10 –3 –5.7 × 10 −1 ng/mL with a detection limit of 1.65 × 10 –4 ng/mL ( S / N = 3). The findings open new avenues for the clinical detection of low-concentration cancer biomarkers, offering promising prospects for early diagnosis and improved patient outcomes.